2021
DOI: 10.3389/fcell.2021.658856
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Regulator-Related Molecules Can Be Used as Prognostic Biomarkers for Glioblastoma

Abstract: IntroductionSUMOylation is one of the post-translational modifications. The relationship between the expression of SUMOylation regulators and the prognosis of glioblastoma is not quite clear.Materials and MethodsThe single nucleotide variant data, the transcriptome data, and survival information were acquired from The Cancer Genome Atlas, Gene Expression Omnibus, and cBioportal database. Wilcoxon test was used to analyze differentially expressed genes between glioblastoma and normal brain tissues. Gene set enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…We found that RBM8A-related candidate mRNAs were strongly associated with prognosis of GBM patients, especially ANK1 and MYO15A. These results echo previous studies linking these two mRNAs to GBM prognosis (Serão et al, 2011;Li and Meng, 2021). Methylation of the ANK1 gene changes during development, and this is important for regulating formation of the nervous system (Gasparoni et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…We found that RBM8A-related candidate mRNAs were strongly associated with prognosis of GBM patients, especially ANK1 and MYO15A. These results echo previous studies linking these two mRNAs to GBM prognosis (Serão et al, 2011;Li and Meng, 2021). Methylation of the ANK1 gene changes during development, and this is important for regulating formation of the nervous system (Gasparoni et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…However, high expression has been associated with better prognosis in some cancer types. Downregulated expression levels in cancer tissues have consistently been reported for SENP2 [52][53][54][55][56][57] and PIAS2 [58][59][60]. The prognostic value of a single SUMO machinery component can also vary between cancer (sub)types, and, e.g., the value for PC2 [61,62] and PIAS4 [63,64] as prognostic biomarkers in breast cancer and for PIAS3 [65,66] in mesothelioma remains ambiguous (Table 1).…”
Section: Altered Expression and Prognostic Significance Of Sumo Pathway In Cancermentioning
confidence: 99%
“…To improve prognostic and predictive survival power in GBM patients, researchers [ 69 , 91 92 , 94 95 , 97 , 109 , 131 , 137 138 , 144 , 147 , 172 , 186 , 189 , 195 , 197 , 200 , 222 , 242 , 251 , 253 ], identified a panel of 2, 3, 4, 6,7, 8, 13, or 14 genes using mRNA expression datasets. They established a risk score model that performed well in survival prediction.…”
Section: Discussionmentioning
confidence: 99%